The effect of mathematical modeling activities on primary school students’ number sense and attitudes towards mathematics - Savaşlı, Büşra; Serin, Mehmet Koray (Ordu University, 2025)
In this study, the effects of mathematical modeling activities on fourth grade students' number sense and attitudes towards mathematics were examined. The study, which was designed with a quasi-experimental unbalanced pretest-posttest control group design from quantitative research methods, was conducted with fourth grade students studying in a public primary school located in Van city center. The Number Sense Test (NST) developed by Çekirdekci (2015) and the short form of the Attitude Towards Mathematics Instrument (ATMI) adapted by Hacıömeroğlu (2017) were used as pretest and posttest in the study. In the experimental group, the lesson was taught with mathematical modeling activities designed by the researcher, while in the control group, the lesson was continued in accordance with the current curriculum. Post-tests were administered after 10 weeks of activities. Independent groups t-test and Mann-Whitney U tests were used to analyze the data. According to the findings obtained from the research, it was seen that there was a significant difference in the NST pre-test and post-test scores of the experimental group. In the control group, no significant difference was found for NST. A significant difference was found between the pre-test and post-test scores of the experimental group in the ATMI, but no significant difference was found in the control group. When the NST scores between the groups were examined, a significant difference was found between the experimental and control groups, and this difference was in favor of the experimental group. According to the ATMI scores, a significant difference was found between the experimental and control groups. This difference was in favor of the experimental group. From the data obtained, it was concluded that mathematical modeling activities had a positive effect on students' number sense and attitudes towards mathematics.